2014
DOI: 10.1126/science.1260282
|View full text |Cite
|
Sign up to set email alerts
|

Seeking out Majorana under the microscope

Abstract: A chain of iron atoms on lead may reveal a signature of the elusive Majorana particle [Also see Research Article by Nadj-Perge et al. ]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…[4] and [5], respectively for semiconducting nanowire and magnetic adatom systems in the presence of strong spin-orbit and magnetic fields with an s-wave superconducting surface. In the experiments above, it is not clear whether the ZBPs are due to a genuine isolated MQP or associated with disorder introduced by ordinary fermionic states lying within the superconducting gap, crossed Andreev effect, among others [6][7][8] . Furthermore, thermal broadening together with a coherence length much longer than the Kitaev chain size can also lead to the overlap of the MQPs at the chain edges, thus suppressing the ZBP signature 8 .…”
Section: Introductionmentioning
confidence: 99%
“…[4] and [5], respectively for semiconducting nanowire and magnetic adatom systems in the presence of strong spin-orbit and magnetic fields with an s-wave superconducting surface. In the experiments above, it is not clear whether the ZBPs are due to a genuine isolated MQP or associated with disorder introduced by ordinary fermionic states lying within the superconducting gap, crossed Andreev effect, among others [6][7][8] . Furthermore, thermal broadening together with a coherence length much longer than the Kitaev chain size can also lead to the overlap of the MQPs at the chain edges, thus suppressing the ZBP signature 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite such a great progress in the observation of (Majorana) edge modes in ferromagnetic atomic chains on a superconducting surface, some loose ends remain to contend with [10]. In fact, it was clear from the estimates [2,11] that Majorana edge fermions in finite-length (of the size L) quantum chains have to hybridize to form a conventional Dirac fermion with the energy proportional to exp( / ), L where is the coherence length of the superconducting chain.…”
mentioning
confidence: 99%
“…In this situation, the opposite case L can persist, which means that Majorana edge states strongly hybridize to form a Dirac fermion with essentially nonzeroenergy. The short-distance physics of open superconducting chains with edge Majorana modes is not yet fully understood [10]. Then, the goal of the present study follows: to investigate analytically how the energy of bound edge states in open superconducting chains depends on the length.…”
mentioning
confidence: 99%
“…To conclude, it is interesting to note that Nadj-Perge et al reported the observation of Majorana fermions in a chain of Fe atoms, which intrinsically have ferromagnetic nature, on a superconducting Pb substrate [13,14]. It is also noted that the recent developments in the field of cold atoms open a route to the experimental realization of one-dimensional interacting fermion systems [22].…”
Section: Resultsmentioning
confidence: 93%